IDENTIFYING ENVIRONMENTALLY-CONSCIOUS SEGMENTS OF TOURISTS TO THE BIODIVERSITY-RICH DESTINATIONS OF NORTH-EAST INDIA - DEY, BANASREE (ASEAN Journal on Hospitality and Tourism, 2013)
Destinations with rich biodiversity can provide an enriching experience to tourists. However, such areas are faced with concerns about depletion of natural resources and tourism may have negative impacts on biodiversity. For areas such as the ‘biodiversity hotspot’ North-east India sustainable tourism offers an opportunity in terms of conservation of biodiversity and sustainable use of its components. The concept of ‘market-driven’ sustainable tourism, aims at attracting tourists who have an environment-orientation. The purpose of this study is to identify segments of tourists visiting North-east India that display sensitivity to the natural environment. A combination of hierarchical and k-means Cluster analysis has resulted in three segments – passive players, environmentally-conscious tourists and sustainable tourists. These have displayed significant differences with regard to demographics, travel-related variables and vacation preferences. The results have interesting implications for destination marketers who may gain useful insights regarding the environmentconscious segments of tourists to this biodiverse region of the country.